2013
DOI: 10.1155/2013/125027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Immunomodulatory, and Cytotoxic Action of Fractions from Eugenia uniflora L. and Eugenia malaccensis L.: Correlation with Polyphenol and Flavanoid Content

Abstract: An increasing number of biological activities presented by medicinal plants has been investigated over the years, and they are used in the search for new substances with lower side effects. Eugenia uniflora L. and Eugenia malaccensis L. (Myrtaceae) have many folk uses in various countries. This current study was designed to quantify the polyphenols and flavonoids contents and evaluate the immunomodulatory, antioxidant, and cytotoxic potentials of fractions from E. uniflora L. and E. malaccensis L. It was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
1
12
0
9
Order By: Relevance
“…The ethyl acetate fraction had the highest antioxidant property. This agrees with the deduction made in other studies which revealed that the ethyl acetate fraction of E. uniflora leaf extract contains higher antioxidant potential compared to the butanol and aqueous fractions of the same extract as a result of higher polyphenols content in ethylacetate fraction 23 . Likewise, polyphenolic compounds have been found to possess a wide range of bioactivity potential and have been indicated by the high activity of fruit extract of Eugenia uniflora in DPPH antioxidant assay compared to the activities of fruit extracts of over thirty edible tropical fruits 24 .…”
Section: Phytochemical Screeningsupporting
confidence: 93%
“…The ethyl acetate fraction had the highest antioxidant property. This agrees with the deduction made in other studies which revealed that the ethyl acetate fraction of E. uniflora leaf extract contains higher antioxidant potential compared to the butanol and aqueous fractions of the same extract as a result of higher polyphenols content in ethylacetate fraction 23 . Likewise, polyphenolic compounds have been found to possess a wide range of bioactivity potential and have been indicated by the high activity of fruit extract of Eugenia uniflora in DPPH antioxidant assay compared to the activities of fruit extracts of over thirty edible tropical fruits 24 .…”
Section: Phytochemical Screeningsupporting
confidence: 93%
“…Some authors have correlated the immunomodulatory effects with the antioxidant status [75] reported that higher antioxidant capacity of E. malaccensis L. and E. uniflora L. helped to reduce the inflammatory response in in vivo. Plant extracts with antioxidant activity could also have immunomodulatory ability [76] .…”
Section: Resultsmentioning
confidence: 99%
“…The total flavonoid content of M. floribunda leaves was higher than those reported for other Myrtaceae species, such as Eugenia uniflora (8.43%), Eugenia malaccensis (4.07%), Eugenia brasiliensis (5.41%), Eugenia beaurepaireana (11.46%) and Eugenia umbelliflora (3.28%) (Figueirôa et al 2013, Magina 2008. This result may be explained because the species M. floribunda lives in areas of sandbank, which is a hostile environment for vegetal growth, and also its flavonoids antioxidant propriety protects the vegetal tissue from the extensive luminosity (Zuanazzi and Montanha 2004).…”
Section: Resultsmentioning
confidence: 58%